Investigating The Efficacy of Ruxolitinib and CHIR-99021 in Targeting Pediatric Neuroblastoma Stem Cells - Al Sayyed, Fatima (2021)
Neuroblastoma is the most common malignant tumor of infancy and accounts for 10% of all childhood cancers. The high biological and clinical heterogeneity of this tumor leads to differences in clinical outcomes ranging from benign tumors that regress spontaneously to metastatic tumors that are ultimately fatal. Despite the recent advances, many children continue to suffer from refractory and relapsed diseases, and they often develop metastatic tumors resistant to standard treatments. Amplification of MYC-N proto-oncogene is highly associated with clinically aggressive disease, recurrence and treatment failure. The highly malignant rate in neuroblastoma is likely due to the continuous acquisition of genetic aberrations in undifferentiated neuroblastoma cancer stem cells (CSCs). CSCs play a crucial role in dysregulating different pathways that are involved in metastasis, invasion, angiogenic properties, uncontrolled proliferation, self-renewal capacities and therapeutic resistance. In this study, we investigate the efficacy of two small molecules Ruxolitinib, a JAK/STAT inhibitor, and CHIR-99021, a GSK-3 inhibitor, in targeting pediatric neuroblastoma stem cells by testing them on human MYC-N amplified, IMR-32, and non-MYC-N amplified, SK-N-SH, cell lines. Treating neuroblastoma cells with Ruxolitinib and CHIR-99021 resulted in significant reduction in cellular proliferation, viability, apoptosis and tumorsphere formation capacity in both IMR-32 and SK-N-SH cell lines. Western blot analysis showed significant decrease in stem cell markers SOX-2 and Oct-4, and tumorigenic protein HMGA1, whereas it showed significant increase in apoptotic markers cleaved PARP and cleaved caspase-3. In conclusion, our findings demonstrated that Ruxolitinib and CHIR-99021 could be promising therapies in targeting neuroblastoma CSCs, and that combining these two drugs may have added therapeutic effects in treating this malignant tumor. Further studies are warranted to elucidate the therapeutic mechanism through which these drugs act to target the various tumorigenic pathways.